The evaluation of gastroesophagel reflüx incidence in children with various symtoms by cintigraphy - Ahmet YARAMIŞ; Fuat GÜRKAN; Kenan HASPOLAT; Bünyamin DİKİCİ and Orhan DERMAN and Murat SÖKER and Süleyman YILMAZ (Turkish Journal of Gastroenterology, 2019)
-